Assessment of the water and sediments quality around the coastal submarine sewage outfall in Guarujá, São Paulo, Brazil (Research, Society and Development, 2021)
The discharge of domestic sewage is one of the most common types of marine pollution, namely through submarine outfalls. In this study, water and sediments of the coastal submarine sewage outfall in Guarujá, São Paulo, Brazil were assessed during the high (January) and low (April) tourist seasons in 2018. The Canadian Council of Ministers of the Environmental Water Quality Index (CCMEWQI) showed a “marginal” water quality, in both seasons, where dissolved oxygen, biochemical oxygen demand, oil and greases, ammonia, surfactants, aluminium, lead, copper, nickel, Escherichia coli and Enterococci showed potential ecological risks. However, no mutagenic potential was detected in the complex mixture (Ames Salmonella/microsome test: MI